Imposition of Criminal Sanction Against Sexual Offenders from the Perspective of Child Protection Laws - Dian Ety Mayasari (Universitas Airlangga, 2022)
While the Indonesian government has passed the Law on Child Protection to ensure the fulfillment of children's rights, there remain a substantial number of children who are victims of sexual violence. In fact, the cases reached 14,517 in 2021. For that reason, this paper aims to discuss the imposition of criminal sanction against sexual abusers and law protection for child victims of sexual abuse. This paper is a normative legal research that puts emphasis on the legal approach, especially the Child Protection Law. Regulations on procedures for imposition of sanction against sexual offenders are already included in the Child Protection Law, despite the fact that sanctions are not explicitly defined since there are minimum and maximum criminal sanctions. Therefore, it is perceived that judges can impose minimal criminal sanctions, including chemical castration, which is one of the additional sanctions as regulated in Law Number 17 of 2016. For those categorized as child victims, psychological advocacy is important to recover their mental condition and to move on from past trauma. This has been regulated as special protection that takes the forms of reproductive health education, inculcation of religious values and decency; social rehabilitation; psychosocial advocacy toward healing; and protection and advocacy at every stage of trial, from investigation, prosecution, up to examination in court. Imposition of criminal sanctions against the offender and advocacy for child victims of sexual abuse must be optimally implemented to ensure their optimal growth and development to become this country’s future generation that succeed in making their dream come true.